2019
DOI: 10.1177/0300060519883090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capacitive and resistive electric transfer therapy in patients with painful shoulder impingement syndrome: a comparative study

Abstract: Objective Capacitive and resistive electric transfer therapy (CARE) reduces pain and improves quality of life for many orthopaedic degenerative and inflammatory disorders. The research aim was to determine the effects of CARE on painful shoulder. The outcomes were pain reduction and recovery of shoulder function. Methods A retrospective, observational case-control study was conducted. Participants were 46 patients (22 in the CARE group and 24 in the SHAM group). Clinical data, pain (visual analogic scale, VAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…TT produces a thermal effect, assumed to be a biological effect related to hyperthermia. Our results are similar to previous studies regarding the temperature due to its increase after applying the technique [4]. For instance, the study of Benito et al [17] found no significant differences between groups in skin temperature assessed by thermography, as was also the case in our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…TT produces a thermal effect, assumed to be a biological effect related to hyperthermia. Our results are similar to previous studies regarding the temperature due to its increase after applying the technique [4]. For instance, the study of Benito et al [17] found no significant differences between groups in skin temperature assessed by thermography, as was also the case in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Current evidence describes an increase in tissue elasticity after TT [4]. Such increased tissue flexibility was not evident in ankle ROM measurements in the current study.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In addition, the horses were subjected to only four sessions and probably a higher number of sessions would have resulted in more evident accelerometric changes. In fact, between 6 and 10 sessions have been reported to result in improved function and disability and reduced pain in human beings with low back pain [21], myofascial chronic pain [22], knee osteoarthritis [23,38] and shoulder impingement syndrome [39].…”
Section: Discussionmentioning
confidence: 99%